The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s13053-017-0071-z
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative genetic testing impacts surgical decision making in BRCA mutation carriers with breast cancer: a retrospective cohort analysis

Abstract: BackgroundThe impact of timing of genetic testing on surgical decision making in women with breast cancer and BRCA mutation is not well known.MethodsWomen who were found to carry a deleterious BRCA mutation and had been diagnosed with breast cancer were identified from a database at Beaumont Health. Women who had received BRCA positive results at least a day prior to their index surgery were considered to be aware of their mutation status prior to surgery. Baseline characteristics and surgical choices were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 40 publications
3
19
0
Order By: Relevance
“…Clinic-based studies have established that when newly diagnosed breast cancer patients receive genetic testing results prior to their definitive breast cancer surgery, over 50% of mutation carriers opt for immediate bilateral mastectomy (BLM) [1420]. However, identification and referral of newly diagnosed high-risk breast cancer patients is suboptimal.…”
Section: Introductionmentioning
confidence: 99%
“…Clinic-based studies have established that when newly diagnosed breast cancer patients receive genetic testing results prior to their definitive breast cancer surgery, over 50% of mutation carriers opt for immediate bilateral mastectomy (BLM) [1420]. However, identification and referral of newly diagnosed high-risk breast cancer patients is suboptimal.…”
Section: Introductionmentioning
confidence: 99%
“…Variants in CHEK2 and ATM can impact cancer surveillance and cancer screening, as well as prevention for blood relatives 40,41 . For our patients, the discovery of these actionable germline mutations led to recommendations for increased breast cancer surveillance with the addition of screening breast MRIs (for both ATM and CHEK2 mutation carriers) and more frequent colonoscopies for colon cancer surveillance (for CHEK2 mutation carriers only) 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The rate of mutations in women who has developed both ovarian and breast cancer was 27.8% and in males with breast cancer, 11.5% (21). Studies have demonstrated that women who know their BRCA status before surgery are more likely to opt for bilateral mastectomy (i.e., contralateral riskreducing mastectomy) than those who do not have this information (22,23). Moreover, the presence of a mutation allows predictive testing of relatives, hence identifying other family members at high risk.…”
Section: Genetic Testing-brca1 Brca2 and Tp53mentioning
confidence: 99%